Discovery Two Potent and New Inhibitors of 15-Lipoxygenase: (E)-3-((3,4-Dihydroxybenzylidene) Amino)-7-Hydroxy-2h-Chromen-2-One and (E)-O-(4-(((7-Hydroxy-2-Oxo-2h-Chromen-3-Yl) Imino)Methine) Phenyl)Dimethylcarbamothioate - Mascayano-Collado, C (Birkhauser Boston, 2017)
The mechanisms of action and structural determinants of lipoxygenases inhibitors have been explored on several occasions, but many questions remain unanswered, especially about the differences of the inhibition mechanisms and their effect on the selectivity of lipoxygenases isoenzymes. Thus, REDOX mechanism has been proposed in this research to clarify the lipoxygenases inhibition by coumarins derivates on 15-sLOX. A series of fifteen coumarin derivatives were synthetized and evaluated as 15-lipoxygenase inhibitors. The results showed that some molecules had submicromolar activities and compete with the substrate as we observed by kinetic studies. The most relevant and interesting result was found for compound 6 who showed an inhibitory activity comparable to nordihydroguaiaretic acid a potent and REDOX inhibitor of lipoxygenases (0.17 and 0.29 μM, respectively). Finally, the docking and molecular dynamics studies showed that the better ligands were accommodated into the binding site being related with those obtained biological data. In addition, our findings contribute at the understanding of inhibitor structural requirements and elucidate the inhibition mechanism of cumarin derivatives on 15-sLOX. Thus, we point to new parameters for the future design of new ligands with potential therapeutic utility where are involved the lipoxygenases enzymes. © 2017, Springer Science+Business Media, LLC.